Survival and Living Situation After Ruptured Abdominal Aneurysm Repair in Octogenarians. (March 2021) - Roosendaal, Liliane C.; Wiersema, Arno M.; Yeung, Kak K.; Ünlü, Çağdaş; Metz, Roderik; Wisselink, Willem; Jongkind, Vincent
Abstract : Objective: To determine the 30 day and one year mortality and post-operative living situation in octogenarians treated for ruptured abdominal aortic aneurysm (rAAA). Methods: A retrospective study was performed at four centres in the Netherlands. All consecutive patients aged ≥80 years, presenting with a rAAA between January 2013 and October 2018, were included. The primary outcomes were post-operative living situation and one year mortality. Results: In total, 157 patients were included. Forty-seven received palliative care and 110 patients had surgery. After endovascular or open repair, the one year mortality rate was 50.0%. The 30 day mortality rate was 40.8% (95% confidence interval [CI] 27–55) and 31.7% (95% CI 20–44), for endovascular and open repair, respectively ( p = .32). Sixty-five per cent of survivors were discharged home, while 34.8% went to a nursing home for rehabilitation. Of the surviving patients, 82.6% went back to living in their pre-rupture home situation. Of the investigated variables, only a high body mass index proved a significant predictor of death at 30 days and one year. Compared with operated patients, patients turned down for surgery were older (mean age 87.5 ± 3.8 vs. 84.0 ± 3.5; p < .001), lived significantly more often in a nursing home (odds ratio 1.02, 95% CI 1.00–1.03; p < .001), were more often dependent (odds ratio 3.69, 95% CI 2.31–5.88; p < .001) and had a lower Glasgow Coma Scale score on arrival (odds ratio 0.42, 95% CI 0.25–0.69; p = .002). All palliative patients died within three days. Conclusion: Overall treatment outcomes showed that octogenarians should not be denied surgery based on age alone, as half of the octogenarians that undergo surgical treatment are still alive one year after rAAA repair. In addition, > 80% returned to their own home after rehabilitation.